2015
DOI: 10.5152/balkanmedj.2015.15884
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Anti-Inflammatory Effect of H1 Antihistamines in Allergic Rhinitis: A Randomized Clinical Trial

Abstract: Background: Allergic rhinitis is characterized by a chronic inflammation of nasal mucosa and represents a risk factor for asthma occurrence. H1 antihistamines reduce the symptoms of rhinitis, but some compounds may have anti-inflammatory properties. Aims: We evaluated the plasma level of some cytokines in patients with persistent allergic rhinitis (PAR) and their evolution after a 4-week treatment with H1 antihistamines, as well as the risk of asthma after 1.5 years. Study Design: Randomized clinical trial. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
2
13
1
2
Order By: Relevance
“…As such, AR treatment often involves the use of H1 antihistamines which block histamine release. 17 In our study, our results show that both 80 and 160 μmol/L of geraniol are able to stop histamine release by activated HMC-1 cells. This indirectly indicates that geraniol can inhibit mast cell degranulation.…”
Section: Discussionsupporting
confidence: 57%
“…As such, AR treatment often involves the use of H1 antihistamines which block histamine release. 17 In our study, our results show that both 80 and 160 μmol/L of geraniol are able to stop histamine release by activated HMC-1 cells. This indirectly indicates that geraniol can inhibit mast cell degranulation.…”
Section: Discussionsupporting
confidence: 57%
“…Another study conducted by Leaker et al analysed whole‐genome expression profiles of AR patients and observed type 2 inflammation upregulation involving IL‐1β. Bocşan et al measured plasma IL‐1β levels in patients with persistent AR after H1 antihistamine treatment and found that H1 antihistamines reduced plasma the IL‐1β levels and symptoms of AR. In an OVA mouse model of induced AR, researchers have shown that the serum concentrations of IL‐1β and the nasal septum levels of caspase‐1 in the OVA group were significantly higher than those in the control group.…”
Section: Role Of Il‐1β and Il‐18 In Armentioning
confidence: 99%
“…The mast cell activation sites were associated with allergic reaction and IL‐1β production . Antihistamine drugs reduced the pro‐inflammatory markers in the allergic reactions and improved the symptoms . In this study, β‐eudesmol inhibited the PCA reaction and levels of histamine, IgE, IL‐1β, IL‐4, IL‐5, IL‐6, IL‐13, and VEGF in the serum of mice under PCA.…”
Section: Discussionmentioning
confidence: 56%